Cross Borders : International Visual Arts Project. - Cromack, Gary; Healey, Gregory (Leeds : [s.n.], 1993)
Binder, Peter ; Bürger, Sabine ; Clevers, Jos ; Cromack, Gary ; Dien, Phan Kim ; Fekete, Gabriella ; Goertz, Pit ; Gulbrandsen, Morten ; Healey, Gregory Paul ; etc.
Cross Borders has been initiated and organised by Gary Cromack and Gregory Healey
Cross Borders : International Visual Arts Project, Leeds, June 15th - July 15th, 1993
boek